Aging of 3Y-TZP dental zirconia and yttrium depletion. Issue 11 (November 2017) - Pandoleon, P.; Kontonasaki, E.; Kantiranis, N.; Pliatsikas, N.; Patsalas, P.; Papadopoulou, L.; Zorba, T.; Paraskevopoulos, K.M.; Koidis, P.
Highlights: High luminescence before aging was correlated to high amount of oxygen vacancies. Aging is accompanied by a significant loss of yttrium from the surface. Surface oxygen vacancies decrease after aging. Yttrium removal from the lattice leads to the formation of Y2 O3 on the surface. Abstract: Objective: Yttrium-stabilized zirconia is susceptible to low temperature degradation after interaction with water. Various mechanisms by which water molecules destabilize the tetragonal phase have been proposed, while the concept of yttrium depletion by the incorporation of hydroxyl ions in the crystalline structure either through the formation of YOH/ZrOH bonds or small α-Y(OH)3 crystallites, is prevailing. The present study was performed to investigate the surface alterations on a 3Y-TZP dental ceramic during the process of in-vitro aging and to further explore the yttrium depletion mechanism that occurs upon interaction with water. Methods: Surface structural changes of zirconia specimens where investigated before and after in-vitro aging with X-ray diffraction analysis, Fourier-transformed infrared spectroscopy, X-ray photoelectron spectroscopy, fluorescence microscopy and scanning electron microscopy. Results: High luminescence generated from the non-aged specimen was explained by the high amount of oxygen vacancies. The phase transformation from the t-ZrO2 to the m-ZrO2 phase after aging was accompanied by a significant loss of yttrium, a clear decrease of oxygen vacancies and a profound decrease of luminescence. Surface oxygen vacancies either migrated into the inner of the specimens or/and/engaged oxygen from the ZrO2 and formed the metallic phase of Y2 O3 on the surface after aging. Significance: An "ideal" amount of oxygen vacancies that could stabilize the tetragonal phase in Y-TZP zirconia ceramics, without compromising esthetics and LTD resistance, is still a matter of further research and different susceptibilities to LTD among various dental zirconia ceramics are based on the amount of oxygen vacancies that can be annihilated by water molecules.